TINDAK PIDANA PENGGUNA IJAZAH PALSU STUDI KASUS PENGADILAN NEGERI KUPANG NOMOR 355//PID.SUS.2015//PN.KPG. - Hendrikus Iswanto Sambarita (Kerta Dyatmika, 2020)
Fake diploma which is a criminal act which is regulated in article 263 of the Criminal Code, and specifically regulated in article 68 of Law No. 20 of 2003 concerning the National Education System and article 93 of Law No. 12 of 2012 concerning Higher Education, for that person to obtain the diploma must go through the educational process in accordance with the applicable rules so that the diploma used can be used properly and it is recognized that someone has passed a certain education, in the case of using fake diplomas there are several legal rules governing the use of diplomas and degrees, generally article 263 of the Criminal Code and specifically regulated in article 68 of Law No. 20 of 2003 concerning the National Education System and article 93 of Law No.12 of 2012 concerning Higher Education, in this case the judge decides to use article 68 Paragraph 2 against the perpetrator using a diploma and a fake Doctorate degree on case No.355 / PID.SUS / 2015 / PN.KPG. where in the concept of criminal law we recognize the principle of the Lex superior derogate legi afriori principle of legal interpretation which states that higher law excludes lower law. This study uses a method of normative legal research or literature study where the type of approach taken is the type of legislative approach (the statuta aproach) approach to legal argumentation (legal reasoning) and the approach of analyzing legal concepts and court decisions, with argumentation and systematization techniques, to knowing ; whether the legal sanctions that can be used by judges in making decisions against perpetrators of fake diploma users and how is the criminal responsibility against the use of fake diplomas, whether the verdicts of the Kupang District Court judges are appropriate to give a redundant effect on the perpetrators. It is hoped that in the case of the crime of forgery of the diploma the author expects law enforcement from the police to be more careful of the process of assigning suspects based on evidence and prosecutors in making indictments to be more careful in applying the articles before delegation to the Panel of Judges so that judges in receiving, examining and adjudicate cases more thoroughly against the facts revealed in the trial and pay more attention to the legal basis that will be applied to the perpetrator, in deciding the case so that it does not become a norm conflict in its application. Key words: Crime, Fake Diploma